Going Back to Einstein's 1907 in the Modern Computer Age - Rossler, Otto E.; Kolb, Yaël; Ujica, Andrei (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2019)
Einstein’s equivalence principle of 1907 amounts to a mental analog computer that is ready for simulation in the modern computer age. Several new fundamental implications do already come to the fore in the process of merely preparing to do so. They are as revolutionary as one is used to from Einstein’s brain children.